The crescendo pulse frequency of shear stress stimulates the endothelialization of bone marrow mesenchymal stem cells on the luminal surface of decellularized scaffold in the bioreactor. Issue 3 (1st March 2022) - Jiao, Yuhao; Zhang, Yuanguo; Xiao, Yonghao; Xing, Yuehao; Cai, Zhiwen; Wang, Cong; Zhou, Zhengtong; Feng, Zengguo; Gu, Yongquan
ABSTRACT: A completely confluent endothelial cell (EC) monolayer is required to maintain proper vascular function in small diameter tissue-engineered vascular graft (TEVG). However, the most effective method for EC attachment to the luminal surface and formation of an entire endothelium layer that works in vitro remains a complicated challenge that requires urgent resolution. Although pulsatile flow has been shown to be better suited for the generation of functional endothelium, the optimal frequency setting is unknown. Several pulsatile flow frequencies were used to implant rat bone mesenchymal stem cells (MSC) into the lumen of decellularized porcine carotid arteries. The endothelium's integrity and cell activity were investigated in order to determine the best pulse frequency settings. The results showed that MSC were maximally preserved and exhibited maximal morphological changes with improved endothelialization performance in response to increased pulse stimulation frequency. Increased pulse frequency stimulation stimulates the expression of mechanoreceptor markers, cytoskeleton reorganization in the direction of blood flow, denser skeletal proteins fibronectin, and stronger intercellular connections when compared to constant pulse frequency stimulation. MSC eventually develops an intact endothelial layer with anti-thrombotic properties on the inner wall of the decellularized tubular lumen. Conclusion: The decellularized vessels retain the three-dimensional structure of the vasculature, have a surface topography suitable for MSC growth, and have good mechanical properties. By increasing the frequency of pulsed stimulation, MSC endothelialize the lumen of the decellularized vasculature. It is expected to have anti-thrombotic and anti-neointimal hyperplasia properties after implantation, ultimately improving the patency of TEVG.